2019
DOI: 10.4049/jimmunol.202.supp.140.15
|View full text |Cite
|
Sign up to set email alerts
|

CD4+ T cells Promote Humoral Immunity and Viral Control during Zika Virus Infection

Abstract: Several Zika virus (ZIKV) vaccines designed to elicit protective antibody (Ab) responses are currently under rapid development, but the underlying mechanisms that control the magnitude and quality of the Ab response remain unclear. Here, we investigated the CD4+ T cell response to primary intravenous and intravaginal infection with ZIKV. Using the LysMCre+Ifnar1fl/fl (myeloid type I IFN receptor-deficient) C57BL/6 mouse models, we identified six I-Ab-restricted ZIKV epitopes that stimulated CD4+ T cells with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…For example, while truncated prokaryote-expressed E ZIKV (30) or EDIII ZIKV (31) were shown to induce high titers of neutralizing antibodies, no difference in immunogenicity and protection were obtained when a version of the E protein (E80) was produced in eukaryotic and prokaryotic systems (40). CD4 + T cells is essential for the protective immunity against ZIKV, since their depletion reduced the generation of anti-ZIKV antibodies (50,60) and CD8 + T cell responses (61). Furthermore, CD8 + T cells are important during flavivirus infections as they contribute to protection in B cell-deficient mice (51), and their lack increases mortality in ZIKVinfected mice (62).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, while truncated prokaryote-expressed E ZIKV (30) or EDIII ZIKV (31) were shown to induce high titers of neutralizing antibodies, no difference in immunogenicity and protection were obtained when a version of the E protein (E80) was produced in eukaryotic and prokaryotic systems (40). CD4 + T cells is essential for the protective immunity against ZIKV, since their depletion reduced the generation of anti-ZIKV antibodies (50,60) and CD8 + T cell responses (61). Furthermore, CD8 + T cells are important during flavivirus infections as they contribute to protection in B cell-deficient mice (51), and their lack increases mortality in ZIKVinfected mice (62).…”
Section: Discussionmentioning
confidence: 99%
“…The results of a phase 1 clinical trial of a ZIKV inactivated vaccine demonstrated that neutralizing antibody response declined significantly by week 16 (52). The sharp drop in neutralizing antibody titers may be related to the poor ability of the inactivated vaccine to induce cellular immune responses, particularly the lack of CD8 + T cells (50). Here, immunization with all ZIKV envelope proteins induced specific IFNg-producing cells as well as CD4 + and CD8 + T cells able to produce IFNg or TNFa, in a similar way.…”
Section: Discussionmentioning
confidence: 99%
“…While neutralizing antibodies are the primary correlates of protection against ZIKV, T cell immunity also plays an important role in controlling Zika infection [ 66 ]. Several experimental mouse models have explored the role of T cells in ZIKV protection [ 67 , 68 , 69 ]. Since cytokines play a key role in activating the immune system and generating an effective immune response, the identification of ZIKV-specific cytokines can help in the selection of target antigens and vaccine formulations.…”
Section: Discussionmentioning
confidence: 99%
“…Full protection against flaviviruses involves a combination of adaptive humoral and cellular responses [ 22 ]. Since many immunodominant epitopes for the induction of T cell-mediated responses are present in non-structural proteins, epitopes or domains of proteins, such as NS1 and NS3, have been included in the design of vaccines, targeting both ZIKV and DENV [ 23 ]. In this context, vaccines based on multiepitope sequences are promising platforms concerning immunogenicity, protection, and safety [ 24 ].…”
Section: Introductionmentioning
confidence: 99%